2023
DOI: 10.29019/enfoqueute.861
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of regression algorithms to protein Plant behavior

Abstract: The behavior of components of protein plant is of vital importance for animals that consume them in their diet. The objective of this research is to evaluate regression algorithms, to determine the behavior of the expressions that best adapt to the procedures of a traditional laboratory and to estimate the chemical components of protein plants, in this sense the MULAN library of java has been used, that contain automatic learning algorithms capable of adapting to dissimilar problems. Three data set were create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Other authors such as Torres-Navarrete, et al, [30] and Torres-Navarrete, et al, [31] associated this behavior with the high proportion of stems in the sample, since N values of approxi-mately 33.6 g kg -1 DM in the leaves are usually reported in the literature, while in the stems it ranges between 11.2 and 22 g kg -1 DM. While Herrera, Verdecia and Ramírez [7], Paumier, et al, [32] and Estrada-Jiménez, et al, [33] found nitrogen concentrations of 26-46 g kg -1 DM. While Verdecia, et al, [34] reported similarities in terms of nitrogen content and variability of T. Diversifolia and G. Sepium, which emphasizes the importance of using the combination of forage species in animal feed.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors such as Torres-Navarrete, et al, [30] and Torres-Navarrete, et al, [31] associated this behavior with the high proportion of stems in the sample, since N values of approxi-mately 33.6 g kg -1 DM in the leaves are usually reported in the literature, while in the stems it ranges between 11.2 and 22 g kg -1 DM. While Herrera, Verdecia and Ramírez [7], Paumier, et al, [32] and Estrada-Jiménez, et al, [33] found nitrogen concentrations of 26-46 g kg -1 DM. While Verdecia, et al, [34] reported similarities in terms of nitrogen content and variability of T. Diversifolia and G. Sepium, which emphasizes the importance of using the combination of forage species in animal feed.…”
Section: Resultsmentioning
confidence: 99%